PENGARUH SOSIALISASI PERPAJAKAN, DIGITALISASI PERPAJAKAN, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KPP PRATAMA DEPOK SAWANGAN - Putra Haris Pradipto (2023)
Taxes are a source of state revenue that has a significant impact on the country's growth. For the state, taxes have an important function because all state expenditures are mostly financed by taxes. This study aims to determine whether there is influence from tax socialization, tax digitization, and tax sanctions on MSME taxpayer compliance at KPP Pratama Depok Sawangan. This study used a quantitative method with MSME tax payers registered at the Depok Sawangan Primary Tax Service Office as a sample. The sampling technique used probability sampling with a total sample of 152 respondents. Data is processed and tested using the Partial Least Square method with the SmartPLS 3.0 application. The results of this study indicate that tax socialization and tax sanctions have a positive and significant effect on MSME taxpayer compliance at KPP Pratama Depok Sawangan. Meanwhile, tax digitization has no effect on MSME taxpayer compliance at KPP Pratama Depok Sawangan.